Numerical research on wear mechanisms of conical cutters based on rock stress state. (March 2019) - Liu, Xiaohui; Tang, Ping; Geng, Qi; Li, Xuan; Tian, Mingrui
Abstract: Conical cutters work on high impact and stress condition, which easily results in failure. The percentage of failure due to wear is about 75%. However, the wear mechanism of conical cutters is still not clear until now. Thus, combining the experiment results existed previously, the numerical simulation model of divided cutter interacted with rock material was established using finite element method. Then, the influence of cutting types and working angles on the rock stress state and the load characteristics was studied to reveal the wear mechanism. The results indicate that the rock mass suffers from compression acted by conical cutter, and the reaction of rock on cutter mainly results in the wear of cutter. The rock stress state and the load characteristics can reflect the wear condition of cutter, which means parts of cutter nearby compression area are subject to severe wear. Moreover, large compression area is always at that far away from the free surfaces. The rake face of cutter bears great load, but it does not wear due to no relative motion between rake face and rock material. On the contrary, there is interference between cutter back face and rock material. And the wear is caused on back face because of the relative motion in the vertical direction of compression. The load under symmetrical cutting type is a little larger than that under asymmetrical condition; the failure area decreases with the cutting angle and increases with incline angle; the mean and mean peak of load on back face decrease with cutting angle, which indicates that large cutting angle should be selected if just for reducing cutter wear; increase of incline angle results in great load asymmetry in cutting process, thus it also causes eccentric wear and premature wear if the cutters have no self-rotatory performance. Graphical abstract: Highlights: Numerical simulation models for linear cutting of divided cutter interacted with rock material was established using finite element method. The influence of cutting types and working angles on the rock stress state and the load characteristics was studied to reveal the wear mechanism.